Tetanus Neonatorum: its Associated Risk Factors and Mortality Rate in Khyber Pakhtunkhwa - Farid Ullah, Farman Ullah, Taj Muhammad, Rida Naz, Mubarik Ali, Norina Jabeen, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Tetanus neonatorum is a preventable cause of mortality and neurological squeal that is more prevalent in resource-poor nations, perhaps because to low rates of mother immunization and unclean cord care procedures. Objectives: The study was conducted in different districts of Khyber Pakhtunkhwa to investigate the prevalence of tetanus neonatorum, its associated risk factors and mortality rate. Methods: This was a retrospective study conducted in five districts of Khyber Pakhtunkhwa during the year 2020-22, through evaluation of the hospital records of 185 tetanus infected neonates, for the assessment of acute risk factors and clinical outcome of the infection. Results: It was found that a significantly higher proportion (p<0.05) of the infected were neonatal fetuses of age less than ten days with the incidence of 83.24%. High mortality rate of 31.35% was observed in the infected infants in which 58 out of 185 infected infants did not survive. Most of the infected patients (p<0.05) were born at home (129/185), through vaginal birth (104/185) and delivered in unhygienic environment (156/185). A significantly high number of women were not immunized against the tetanus infection (p<0.05) and fetal umbilical cords were not managed aseptically and were cut with used razors (12.97%) and fastened with unhygienic threads (38.37%), rendering them vulnerable to the fatal infections. Conclusion: It was concluded that poor tetanus toxoid immunization of the mothers and unhygienic conditions were likely causes. Keywords: Deep wounds; Immunization; Umbilical cord; Unhygienic deliveries.